2014
DOI: 10.1007/s11248-014-9848-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a cystatin transgene can confer resistance to root lesion nematodes in Lilium longiflorum cv. ‘Nellie White’

Abstract: Lilium longiflorum cv. 'Nellie White' assumes a great economic importance as cut flowers, being one of the most valuable species (annual pot plants value above $20,000,000) in terms of wholesales in the US. The root lesion nematode Pratylenchus penetrans (RLN) constitutes one of the main pests for lily producers due to the significant root damage it causes. Our efforts have focused on the generation of soybean hairy roots (as a transient test model) and stable transgenic lilies overexpressing a modified rice c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…As an alternative to RNAi, Vieira et al (113) showed that overexpression of a cystatin OcI D86 transgene can confer resistance to P. penetrans in hairy roots of soybean and Lilium longiflorum plants, with a reduction in nematodes reproduction of 75%. For practical application, a combination of RNAi and expression of a cystatin or a peptide that disorients nematodes (107) might provide the most effective and durable transgenic resistance to RLNs.…”
Section: Gene Silencing In Root Lesion Nematodesmentioning
confidence: 99%
“…As an alternative to RNAi, Vieira et al (113) showed that overexpression of a cystatin OcI D86 transgene can confer resistance to P. penetrans in hairy roots of soybean and Lilium longiflorum plants, with a reduction in nematodes reproduction of 75%. For practical application, a combination of RNAi and expression of a cystatin or a peptide that disorients nematodes (107) might provide the most effective and durable transgenic resistance to RLNs.…”
Section: Gene Silencing In Root Lesion Nematodesmentioning
confidence: 99%
“…Previously, Vieira et al . () identified in the transcriptome of P. penetrans a highly abundant transcript encoding for a FAR gene. Along with the in silico analyses performed in this study, three different FAR members of this family were identified in P. penetrans , and a molecular characterization of the Pp‐far‐1 gene is provided herein.…”
Section: Introductionmentioning
confidence: 99%
“…Nellie White exhibited comparatively high resistant to an endoparasite, Pratylenchus penetrans causing RLN (root lesion disease). OcI Δ D86 expression inhibited parasitic effects of Pratylenchus by 75% in transgenic plants as compared to their wild relatives (Vieira et al, 2015; Table 4). …”
Section: Abiotic and Biotic Stress Tolerancementioning
confidence: 99%